The Semantic Fields Analytical Studies, For the Words of Enmity in the Poems of Eulogy by Poet Uthsman Bin Ishak El-Toradi - Imam, Auwal Ibrahim (Journal of Humanities & Social Sciences, 2019)
The language studies especially the semantics, had been greatly developed, particularly in this present period and It had became the most important issue in human though, because it is the fundamental basic of communication and understanding in community, It is also the root of development and prosperity.The semantics fields are the most important part of modern semantics studies.Such studies have been carried out by some old Arab linguists like: Abi Ubaidat (210. A. H) in his book titled: (Alkhail) the horse. Al- Asmaee (216 A. H) in his book titled: (Khalqu Al- Insaan) Creation of Human. And Ibn- Seedah (448 A. H) In His Book Titled: (AL- Mukhassas) likewise some modern Arab linguists have also contributed to this kind of studies, such as Professor Ahmad Umar Mukhtar, the author of the book (Ilmul- Dilalah) the semantics. Dr. Aliyu AL- Khouli, the writer of the book (Ilmul- Ma’na) science of meaning. DR Ahmad Azooz the author of the book (Usulun Turasiyyah fi Nazariyyatu Al- Huqulu Al- Ddilaliyyah) the Heritage bases in the theory of semantics fields.The convergence of the meaning of words, with different words from each other, is a problematic linguistic phenomenon, and such case can only be solved by studying the words according to the theory of semantic fields, to identify the semantic features, and to detect the semantic relations between words, in this regard, The research Titled; The Semantic Fields Analytical Studies, For the Words of Enmity in the Poems of Eulogy by Poet (Uthsman Bin Ishak El- Toradi) had been carried out.The research Has Discussed A Brief History Of The Poet (Uthsman Bin Ishak El- Toradi), And Also The Paper Talked About The Semantic Analysis Theory In the Light Of Semantic Fields, Explaining Its Importance And Significance In Defining Words Sense And Meanings، Then The Paper Went On To Carry out the Analytical Operation For Words Of Enmity That Were Used In The Poems.
Keywords: the personality of the owner of the Diwan; a poem; the theory of semantic analysis; defining the semantic features; the approach used in the analysis process